Vernacular education in the South Pacific - Siegel, Jeff (International development issues, 1996)
World-wide research has clearly shown the educational, social, cultural and financial benefits of vernacular education - ie using the mother tongue or an already known language of wider communication in the education system. In all 12 South Pacific countries covered by this study vernaculars are used in some form of education but there are many differences among them. The Melanesian countries - Papua New Guinea, Solomon Islands and Vanuatu -have many characteristics in common: an extremely large number of vernacular languages, a widespread lingua franca (Melanesian Pidgin), very low adult literacy rates and low retention rates in the formal education system. In these countries, formal education has been solely in the ex-colonial language or languages (English and French).